UPAYA MENINGKATKAN DISIPLIN GURU DALAM KEHADIRAN MENGAJAR DI KELAS MELALUI PENERAPAN REWARD AND PUNISHMENT DI SMA NEGERI 1 PADANG GELUGUR KABUPATEN PASAMAN - Nelson (Institute of Information Technology and Social Science (IITSS), 2021)
The quality of learning in schools is highly dependent on several factors. A very important factor, among others, is the implementation of a quality improvement school culture. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of discipline, including the discipline of teachers in class attendance in the teaching and learning process. To improve the discipline of teachers can be pursued in various ways. In this School Action Research (PTS), an action was tried in the form of implementing Reward and Punishment for teachers at SMA Negeri 1 Padang Gelugur, Pasaman Regency. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, teacher discipline in class attendance in the teaching and learning process increased and met the predetermined indicators of 75%. From the results of this study, it can be said that to improve teacher discipline in the classroom in teaching and learning activities can be done by applying Rewards and Punishments to teachers.